Influence of soybean meal variety and processing temperature on the growth performance of pigs from 25 to 45 lb - J A Loughmiller; T T Lohrmann; La Llata M De; P R O'Quinn; J C Woodworth; S A Moser; G S Grinstead; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred ninety high-lean growth pigs were used in a 17 d growth assay from 25 to 45 lb. Treatments consisted of soybean meal (SBM) from either high-oleic or check-line soybean varieties processed under pilot-plant processing conditions at four temperature ranges (80-85, 85-90, 90-95, 100-105 °C). Positive and negative controls were made using commercially obtained SBM (46.50%CP). Total dietary lysine was maintained at .95% except for the positive control (1.30%). Pigs fed commercial SBM with 1.30% dietary lysine had increased ADG and better F/G than pigs fed any other treatment. A SBM variety x processing temperature interaction was observed for ADG and F/G for each growth period. The interaction likely resulted from improvement in ADG and F/G with high-oleic SBM, but not the check-line SBM, as processing temperature increased. Pigs fed high-oleic SBM had improved ADG and F/G throughout all growth periods as processing temperature increased, so pigs fed high-oleic SBM processed at 80-85 °C had poorer growth performance than pigs fed any other treatment. These results indicate that pigs fed high-oleic SBM processed above 80-85 °C have similar performance to pigs fed SBM from other varieties.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; High-oleic soybeans; Processsing temperature; Growth; Nursery pigs